Measurement and Prediction of Thermo Physical Properties to Study Intermolecular Interactions of Binary Liquid Mixtures at Various Temperatures by Using McAllister Model - R., Ramesh; K., Ramesh; K., Yusoh (Penerbit Universiti Malaysia Pahang, 2014)

(untitled)
The important of fundamental data for the design and optimization of chemical process are densities and viscosities. The study conducted in this research are viscosities, n, and densities p, of 1,4 Dioxane with two hydrocarbons Benzene and Chloro Benzene have been measured over the entire range of composition at (303, 15, 308,15) K.